Skin reactions after use of antihistamines – a case of urticarial rash induced by loratadine - Lis-Święty, Anna; Brzezińska-Wcisło, Ligia; Bergler-Czop, Beata; Meszyńska, Elżbieta (Dermatology Review/Przegląd Dermatologiczny, 2010)
Introduction . Skin lesions after antihistamine drugs are very rare. However, cases of maculopapular rash, multifocal fixed drug eruption, erythema multiforme, systemic contact dermatitis, generalized, localized urticaria and anaphylactic shock after various drugs from this group have been described. Symptoms may be of allergic origin associated with an immediate mechanism mediated by IgE antibodies or a delayed hypersensitivity reaction. Appearance of skin lesions may also be related to toxic, proinflammatory effects of the drug, which contribute to non-specific activation of mast cells. Objective . To present a case of urticarial rash which occurred after the use of loratadine as a delayed hypersensitivity reaction. Case report . Woman, 60 years old. The first eruption of generalized, erythematous skin lesions resembling urticaria occurred 4 days after the introduction of loratadine. The same type of skin reaction at the re-administration of this drug has confirmed its role as an aetiological factor. Conclusions . Dermatological complications after antihistamines, although rare, may be, in some cases, of a generalized, severe type and require treatment with systemic corticosteroids.